The ECB's climate activities and public trust - Sandra Eickmeier; Luba Petersen (Deutsche Bundesbank, 2024)
As central banks, including the European Central Bank (ECB), adopt climaterelated responsibilities, gauging public support becomes essential. Drawing on a June 2023 Bundesbank household survey, we find that 69% of households report increased trust in the ECB due to its climate actions, valuing the institution's broader scope and concern. While 17% and 20% of households express concerns over risks to price stability or independence, 23% believe climate engagement reinforces the ECB's core objectives. An information intervention indicates minimal impact on household inflation expectations, suggesting a disconnect between institutional trust and inflation outlooks. An internal survey reveals that central bankers accurately gauge trust impacts but tend to overestimate effects on inflation expectations. Overall, our findings indicate broad public support for the ECB's climate initiatives.
Keywords: E7; E59; C93; D84; 330; Central bank trust; central bank credibility; inflation expectations; climate change; green policies; survey; central bank communication; uncertainty